APLIKASI COMPUTATIONAL FLUID DYNAMIC PADA ANALISIS DAMPAK BULBOUS BOW TERHADAP HAMBATAN KAPAL BANTU CAIR MINYAK: Application of Computational Fluid Dynamic in Analyzing The Impact of Bulbous Bow on Resistance of Auxiliary Oil Vessel - Maulidah, Alina Rizka; Karyono, Tri; Priyambodo Nur Ardi Nugroho; Wulandari, Dyah Arum (Jurnal Konversi Energi dan Manufaktur, 2024)
The concept of oil liquid auxiliary vessel combines tanker and container ship features, designed to achieve high speed while maintaining the same displacement, necessitating design analysis to optimize hull resistance. One approach used is the addition of a bulbous bow to the hull. This study compares the resistance between the conventional hull of BCM-3 and the bulbous bow-equipped hull of BCM-4 using computational fluid dynamic (CFD) method with NUMECA. Speed variations used were 16 knots, 17 knots, and 18 knots. The research results show that the use of a bulbous bow on BCM-4 yields more optimal total resistance, with respective resistance values of 339.807 N at 16 knots, 374.558 N at 17 knots, and 497.606 N at 18 knots.